RELIGION AND RESILIENCE OF CHILSDREN IN A HIGHLY SECULARIZED AND DIGITIZED SOCIETY - Dusan Luzny, (PEOPLE: International Journal of Social Sciences, 2025)
In the context of a highly secularised society, religion acquires a new, often less institutional yet still significant role in shaping both individual and collective resilience. Religious traditions, symbols, and rituals function not primarily as sources of doctrinal certainty, but as a cultural reservoir of meanings that can offer support in situations of uncertainty, suffering, or loss. Even where belief in the supernatural has waned, religious language may continue to operate as a mode of existential orientation, helping to mediate a sense of meaning, continuity, and connection with a wider community. Resilience, therefore, is not necessarily contingent upon active religiosity, but can be sustained by the symbolic and ethical resources that religious traditions have left embedded within the cultural memory of a secularised society. In highly secularised societies, the relationship between religion and resilience among children is increasingly mediated by digital culture. Online environments expose young people to a plurality of worldviews and symbolic repertoires. While formal religiosity may play only a marginal role in their lives, digital platforms often serve as spaces where existential questions, ethical dilemmas, and experiences of vulnerability are negotiated. Through social media, gaming, or online storytelling, children encounter hybrid forms of spirituality and community that can foster emotional resilience and a sense of belonging. In this sense, digital culture functions as a new arena in which the symbolic residues of religious traditions are remixed, personalised, and mobilised in support of meaning-making and coping strategies within an ostensibly secular milieu. The conference paper will focus on analyzing the social and cultural environment in Czech society (Europe) and summarize existing data from empirical research. It will identify significant factors and trends that frame the place of religion in a secularized society.